2016
DOI: 10.1007/s00125-016-4116-z
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-induced hyperglycaemia in hospitalised patients: does it matter?

Abstract: Steroid-induced hyperglycaemia is a common problem faced by endocrinologists in hospital wards. In this issue of Diabetologia, Popovic and colleagues (DOI 10.1007/s00125-016-4091-4) have conducted a subanalysis within a randomised controlled trial of prednisone therapy for community-acquired pneumonia. The authors found that the presence of diabetes or hyperglycaemia related to steroid therapy did not attenuate the clinical benefits of steroid therapy. The relevance and possible implications of these findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
1
8
0
1
Order By: Relevance
“…In spite of hyperglycemia, the primary outcome (e.g. time to clinical stability) was not inferior for patients with diabetes and this was confirmed by a regression analysis, supporting the concept that the presence of diabetes or SIH did not modify the benefit of prednisone therapy in this clinical situation [124]. Interestingly, the amount of insulin among patients with diabetes under prednisone was no greater than for those with diabetes on placebo; on the contrary, among patients without diabetes, those administered with prednisone received a larger amount of insulin compared to the placebo group [123].…”
Section: Transient Hyperglycemia: What To Do?supporting
confidence: 56%
“…In spite of hyperglycemia, the primary outcome (e.g. time to clinical stability) was not inferior for patients with diabetes and this was confirmed by a regression analysis, supporting the concept that the presence of diabetes or SIH did not modify the benefit of prednisone therapy in this clinical situation [124]. Interestingly, the amount of insulin among patients with diabetes under prednisone was no greater than for those with diabetes on placebo; on the contrary, among patients without diabetes, those administered with prednisone received a larger amount of insulin compared to the placebo group [123].…”
Section: Transient Hyperglycemia: What To Do?supporting
confidence: 56%
“…[ 25 ] Previous studies showed that 53–70% of individuals without diabetes develop steroid-induced hyperglycemia. [ 26 ] A meta-analysis of 13 studies showed that overall, 32.3% of people developed glucocorticoid-induced hyperglycemia and 18.6% developed diabetes. [ 27 ] In this study, 31 required steroids, of which 11 (35.5%) developed NODM after three months.…”
Section: Discussionmentioning
confidence: 99%
“…Steroid-induced hyperglycemia is common in hospitalized patients. Previous studies show that 53–70% of individuals without diabetes develop steroid-induced hyperglycemia ( 42 ). An Australian study of 80 hospitalized people without diabetes reported that 70% of subjects had at least one blood glucose measurement of ≥10 mmol/L ( 43 ).…”
Section: Potential Mechanisms For New-onset Diabetesmentioning
confidence: 99%